Physical metallurgy of the two–way shape memory effect in TiNi alloys. (4th August 2014) - Filip, Peter; Mazanec, Karel
The two–way shape memory effect in memory alloys is not an inherent characteristic of a material and depends strongly on its structural state. The quantitative parameters (extent of reversible strains, stability, temperature interval and stresses produced during heating and recovery of 'hot shape') crucially depend on the training route performed. The well trained specimens can do work even if the reversible shape memory effect is widely accepted as an unstable one. The transformation temperatures Ms, Mf, As, and Af decrease after training process and cycling under opposing stresses, the TR temperature increases in well trained specimens. The formation of trained martensite variants is thermodynamically favoured with respect to other crystallographically equivalent variants. This favouring effect is ascribed to the dependence of variant energy on the internal stresses connected with specific alternate bands observed in the high temperature phase which were interpreted as 'ghost martensite'.